Using ICT to Patch the Shortcomings of New Public Management in a Post-Communist Welfare State - Sosnowski, Sebastian (Conference on Digital Government Research, 2025)
New Public Management approach in the welfare sector led to outsourcing and disaggregation of the services, which makes it difficult to implement new ICT technologies into such context. In this paper, I analyse the case of Electronic Care System (ECS) implemented in selected municipalities in Poland. These municipalities carry different characteristics of inhabitants and service provision. Additionally, Polish welfare system is a case of transformative system which is a mix of diverse European systems. I analyse secondary data (documents, strategies), interviews and observations regarding the implementation of ECS. Based on that, I draw the main conclusions regarding how context of welfare provision impedes the successful implementation of the ICT within the public institutions. I argue that introduction of ICT in fragmented institutions needs to include diverse perspectives of stakeholders and take into account the values important for the system users. Especially, I focus on how diverse modes of care provision need to be mirrored in the systems, how political and managerial pressures make it more difficult for other actors to navigate through the change. At the end, I ask the question about organisational and cognitive costs of implementing innovations.